Evaluasi Penggunaan Perangkat Lunak Kasir Toko Portable – Point of Sale dalam Sistem Informasi Akuntansi Penjualan Tunai - Fani Yulia Rosyada; Dyah Palupi; Dini Dwi Ermawati (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2022)
This study aims to see the cash sales system implemented and determine whether the application usage in the cash sales system is in accordance with the components of the PIECES analysis method framework. Data collection techniques used are interviews, observation and documentation. The data analysis technique uses the PIECES method which consists of Performance, Information, Economy, Control, Effeciency, and Service. The results showed that the cash sales system used the help of a portable store cashier application - point of sale. Where every cash sales transaction that occurs is inputted and processed to completion and generates daily reports. From the results of the evaluation using the PIECES cash sales information system, it can be said that it is not appropriate with the six elements in the PIECES method.